180 Parent'S Perception of end of Life in Brazilian Pediatric Intensive Care Units. (October 2012) - Lago, P
Abstract : Objective: Assess the parents perception of patients who died in the Pediatric Intensive Care Unit (PICU) about the care given by health staff in the moments preceding the children's death. Methods: Exploratory-descriptive study with a qualitative approach. Settings: 2 PICU in southern Brazil. Subjects: 15 parents of children who died from April to September 2008. Data collection was performed through 3 steps: The researchers contacted the parents by phone call to invite them to attend to the hospitals, The doctors who assisted the children clarified doubts about the therapy offered. A semi-structured interview, was carried out by researchers who had not participated of the care. Results: The analysis resulted in 4 categories: the moment of death in the PICU; talking with the attending physicians; parental involvement in decision making; parental participation in research. The results show that parents lack a peaceful environment where they can adequately carry out the goodbyes at the time of death of their children. They emphasized the solidarity provided by the nursing staff at this point and the little involvement of the medical team. The opportunity to revisit the process of their children's death with the team physician was considered positive. Parents felt that they did not have an effective participation in decision taking. Conclusion: The research shows that the difficulty of communication between health staff and parents is a factor that impacts negatively on the decision taking and grieving processes.